Gerakan Pemberdayaan Kader PTM Hipertensi dalam Program SIGADIS (Aksi Pencegahan dan Deteksi Hipertensi) - Fitriyani Fitriyani; Gabriella Tessalonika; Seyna Adhia Satriana (Warta Pengabdian Andalas, 2024)
In the Baruah Gunuang Public Health Center area, located in Lima Puluh Kota Regency, West Sumatra, the prevalence of hypertension continues to rise, with only 14% of hypertension patients regularly seeking medical check-ups in 2022. Additionally, only 69.44% of patients adhere to regular treatment, far below the target of 100%. To address this issue, community awareness must be increased through the Empowerment Movement of Non-Communicable Disease (NCD) Hypertension Cadres in the SIGADIS Program (Hypertension Prevention and Detection Action). This program aims to enhance the knowledge and skills of cadres in monitoring and managing hypertension within the community. The program was conducted by the Faculty of Public Health at Andalas University in collaboration with the local health center from September to October 2023. Activities included outreach, training, and health screening involving community members appointed as cadres for hypertension prevention in each village. The results of this program showed an increase in the knowledge and skills of the cadres in hypertension prevention and control, as measured by a 5-point increase in pre-test and post-test scores, with no participants scoring below 80 by the end. This improvement in competence is expected to strengthen the role of cadres in education, early detection, and patient recruitment for hypertension, thereby reducing the prevalence of hypertension in the area. The SIGADIS program serves as a community empowerment model for addressing health challenges related to hypertension, particularly in areas with limited access to healthcare services.